AGENT IN DENNY CAKNAN’S HIT SONGS: JANET WOLFF’S SOCIAL PRODUCTION ANALYSIS - Istikomah, Erna; Wilujeng, Nuning Catur Sri; Endraswara, Suwardi; Widyastuti, Sri Harti (IAIN Surakarta, 2024)
This study examines the social ideas embedded in Denny Caknan's hit songs—Kartonyono Medot Janji, Sugeng Dalu, and Los Dol—using Janet Wolff's social production theory. Employing a qualitative descriptive approach, the research integrates intrinsic elements, such as lyrics and music videos, with extrinsic elements, including cultural, social, and personal contexts. The findings reveal that Denny Caknan's works resonate deeply with audiences due to their relatable narratives of heartbreak and resilience, rooted in the Javanese cultural preference for emotionally evocative songs. The